Thyroid Inconveniences With Vaccination Against SARS-CoV-2: The Size of the Matter. A Systematic Review - Caironi, Verdiana; Pitoia, Fabián; Trimboli, Pierpaolo (Frontiers in Endocrinology, 2022)
After the beginning of COVID-19 vaccination campaigns, several reports of thyroid disease possibly related to the Covid-19 vaccination progressively appeared in the literature, raising the question whether the thyroid pathology might be a SARS-CoV-2 vaccine complication. The aim of this study was to analyze the data about COVID-19 vaccination and thyroid disease, in order to evaluate the size and quality of related literature, and the type of these events, and to investigate the timing of onset of these events after vaccination. Pubmed/MEDLINE and Cochrane was systematically reviewed until February 16, 2022, to retrieve the largest number of original papers, case reports, and case series articles reporting thyroid disease after SARS-CoV-2 vaccination; 46 articles were included, describing 99 patients, of which 74.75% female, aged 26 to 73 years. 49.49% of patients received a vaccination with Comirnaty (Pfizer/BioNTech), 14.14% CoronaVac (Sinovac), 12.12% Vaxzevria (Oxford/Astrazeneca), 11.11% Spikevax (Moderna), 3.03% Ad26.COV2.S (Janssen, Johnson & Johnson), one patient Covaxin (Bharat Biotech), one patient Convidecia (Cansino). In 7 cases, the thyreopathy developed after the third dose with a combination of different vaccines. The thyroid diseases were 59 cases of subacute thyroiditis (SAT), 29 cases of Grave’s disease (GD), 2 cases of co-occurrence of GD and SAT, 6 painless thyroiditis, and single cases of thyroid eye disease and hypothyroidism associated with mixedema. The timeline between vaccination and thyroid disorder ranged between 0.5 to 60 days, with an average of 10.96 days. Considering the limited follow-up time, a complete remission was reported in most of SAT and PT cases while a persistence was typical in GD. In conclusion, the size and the quality of published data about thyroid inconveniences after COVID-19 vaccination are limited; thyroid disorders may occur within 2 months after COVID-19 vaccination; among all thyroid diseases after COVID-19 vaccination, GD and SAT seem to be more frequent.